A Development of Swimming Learning Modules to Increase Learning Interest and Learning Efficiency of Swimming Motion Techniques in Beginner Children (Journal of Physical Education and Sports, 2020)
The availability of teaching materials that can increase the activeness and independence of children's learning, especially beginner swimmers in the efficiency of improving the ability of motion techniques, greatly affects the quality and success and ability of students to digest the material and increase their own interest to always be enthusiastic in the swimming learning process. The purpose of this study is to produce swimming learning modules in increasing interest in learning and efficiency of swimming motion techniques in children. The method used in this research is (Research and Development) from Borg and Gall which consists of ten steps. This study uses research instruments in the form of interviews with prospective module users including children and beginner swimmers to find out the response to the module. Based on the student response questionnaire, the results obtained were students' interest and positive responses to the modules that had been made. At the development stage the product was produced in the form of a swimming learning module for beginners, validated by 6 experts, and a questionnaire in response to the module. The module testing phase was conducted in 20 children who are beginner swimmers in several Semarang City clubs. Modules are prepared by taking into account aspects of the accuracy of the contents, digestibility of modules, stages of swimming, module attractiveness, appearance, and use of language and terms. Overall, the modules produced were declared valid and according to the experts included in the criteria were eligible to be used. Modules were produced with design and content components that have been tailored to the needs of users.